IMPACT OF HIGH LEVELS OF CONTINUOUS POSITIVE AIRWAY PRESSURE ON CARDIAC OUTPUT IN PRETERM NEONATES: A PROSPECTIVE PHYSIOLOGICAL STUDY. (18th May 2018) - Mukerji, Amit; Muzafar Wahab, Abdul Gani; Mitra, Souvik; Mondal, Tapas; Paterson, Debie; Beck, Jennifer; Fusch, Christoph
Abstract: BACKGROUND: Many NICUs employ high (>8 cmH2 O) positive end-expiratory pressures (PEEP) on nasal continuous positive airway pressure (NCPAP) to prevent intubation and associated ventilator-induced lung injury, despite limited safety/efficacy data. OBJECTIVES: This study sought to evaluate the physiological impact of high NCPAP PEEP. DESIGN/METHODS: Fifteen preterm neonates at postmenstrual age ≥32 weeks (without congenital anomalies or acute intercurrent illness) on NCPAP PEEP of 5 cmH2 O were enrolled. PEEP was increased by 2 cmH2 O increments until 13 cmH2 O. At each increment, following 5 minutes washout, cardiac output (aortic velocity-time integral x heart rate) and cardiorespiratory parameters including blood pressure, heart rate, respiratory rate were measured over 10 minutes. Predefined cut-off values for changes in cardiorespiratory parameters were used as termination criteria. Data are presented as mean (SD), and were compared using one-way ANOVA. RESULTS: The mean GA, age at study, and weight of subjects were 27.4 (2.6) weeks, 58.5 (35.5) days, and 2.3 (0.6) kg, respectively. Cardiac output (mL/kg/min) at PEEPs of 5, 7, 9, 11, and 13 cmH2 O were not different at 295 (75), 290 (66), 281 (69), 286 (73), and 292 (58), respectively (P=0.986), as shown in Figure 1a. Importantly there were also no differences in either aortic velocity-time integral or heart rate over these PEEP ranges (Figures 1b and 1c). There were no significant differences in cardiorespiratory parameters; no subjects met cut-off criteria. Data collection was terminated in 2 subjects after PEEP 9 cmH2 O due to lung over-distension subjectively noted on echocardiogram. CONCLUSION: High levels of NCPAP PEEP were well tolerated for short durations. Further physiological and clinical research is required on safety/efficacy in neonates with more severe lung disease, as well as its impact over longer durations.